Table 2_Pan-cancer multi-omics characterization of calcyphosine and its revealed links to the immune microenvironment and regulatory networks in endometrial carcinoma.docx - Xi Chen (35903) (2025)
Objective The calcium-dependent activator protein for secretion (CAPS) has emerged as a protein of interest in tumor biology; however, its functional significance in endometrial carcinoma (EC) remains largely unexplored. Methods We performed an integrative analysis leveraging bulk RNA sequencing data from The Cancer Genome Atlas, GTEx, and publicly available EC datasets, coupled with gene set enrichment analysis (GSEA) and single-cell transcriptomic profiling. The association between CAPS expression and clinicopathological parameters as well as patient prognosis was systematically assessed. In addition, functional enrichment, intercellular communication, and immune infiltration analyses were conducted to elucidate the molecular and microenvironmental roles of CAPS. In vitro assays were employed to validate the biological effects of CAPS knockdown on EC cell proliferation, migration, and invasion. Results CAPS was significantly upregulated in early-stage, low-grade, and endometrioid endometrial carcinoma, and its elevated expression was associated with improved patient survival. GSEA indicated that high CAPS expression was correlated with enhanced ribosome biogenesis and oxidative phosphorylation, along with suppression of proliferative signaling, reflecting a metabolically differentiated phenotype. Single-cell transcriptomic analysis revealed that CAPS was specifically enriched in terminally differentiated secretory epithelial cells, promoting epithelial maturation and oxidative metabolism. Furthermore, CAPS-positive cells exhibited extensive crosstalk with immune cells, suggesting a potential role in facilitating anti-tumor immune responses. Functional assays confirmed that CAPS knockdown markedly enhanced EC cell proliferation, migration, and invasion. Conclusion CAPS may act as a tumor suppressor in EC by stabilizing microtubule architecture, reprogramming cellular metabolism, and modulating immune interactions within the tumor microenvironment. These findings highlight CAPS as a promising prognostic biomarker and potential therapeutic target in EC.